Process systems engineering for sustainable photographic lens production: a review - Abdul Razik, Abdul Halim; Yusof@Alias, Firdaus; Buari, Noor Halilah (AIP Publishing, 2023)
Photographic lens is an invention to duplicate human eye functions and operations. Starting with seeing and focusing the object, the lens then transmits lights containing information of the scene such as colours, brightness and shapes to the digital sensor or photographic film. To produce such invention, it comprises complex steps which include material selection and processing, lens machining and finishing. Being the first of its kind, this paper will review the roles of process systems engineering (PSE) in the manufacturing of sustainable photographic lens from R&D and commercial angles. The review will detail PSE contributions for each of the step and highlights the related challenges in implementation.